Penerapan Model Pembelajaran Group Investigation Untuk Meningkatkan Hasil Belajar IPS di Kelas IV SD GMIM I Tomohon - Norma N. Monigir (Peneliti.net, 2021)
This research was conducted based on the results of preliminary observations carried out in class IV GMIM 1 Tomohon Elementary School where based on observations made on social studies learning it was found that the quality of social studies learning was not optimal, because the teacher was less skilled and creative in presenting the material, the teacher only used the lecture method, was rote and the use of props was less attractive to students so that it caused boredom and students were less passionate about learning and had an impact on the achievement of low student learning outcomes. This can be seen from 30 students, only 6 students got high scores and 24 students got poor scores. This study aims to improve social studies learning outcomes through the application of the Group Investigation learning model for fourth grade students of GMIM 1 Tomohon Elementary School. The method used in this research is a Classroom Action Research (PTK) design that refers to the Kemmis and Mc. Taggrat model design which consists of 4 stages namely planning, action, observation, and reflection carried out in two cycles. In the implementation of cycle I student learning outcomes were 64.17% and in cycle II increased to 86%. Thus it can be concluded that the Application of the Group Investigation Model can Improve Social Studies Learning Outcomes of Grade IV Students of GMIM 1 Tomohon Elementary School, which initially in cycle I students did not understand the subject matter and after students were given understanding and evaluation, there was a change in satisfactory learning outcomes in cycle II. Therefore, it is suggested that the fourth grade teacher of GMIM 1 Tomohon Elementary School can use the Group Investigation Learning model because it can improve social studies learning outcomes.